Expression and Truth : On the Music of Knowledge - Kramer, Lawrence, 1946- (Book collections on Project MUSE., 2012)
Expression and truth are traditional opposites in Western thought: expression supposedly refers to states of mind, truth to states of affairs. Expression and Truth rejects this opposition and proposes fluid new models of expression, truth, and knowledge with broad application to the humanities. These models derive from five theses that connect expression to description, cognition, the presence and absence of speech, and the conjunction of address and reply. The theses are linked by a concentration on musical expression, regarded as the ideal case of expression in general, and by fresh reading.